Evaluation of the fouling potential of ceramic membrane configurations designed for the treatment of oilfield produced water. Issue 2 (22nd January 2018) - Ebrahimi, M.; Kerker, S.; Schmitz, O.; Schmidt, A. A.; Czermak, P.
ABSTRACT: During the treatment of oilfield produced water (PW) with ceramic membranes, process efficiency is primarily characterized by the specific permeate flux and the oil separation performance. In addition to membrane properties, the increase in total filtration resistance (fouling) and the decline in permeate flux are strongly dependent on the constituents of the PW as well as process conditions such as trans-membrane pressure and cross-flow velocity. The extensive study presented herein describes the characterization, application and performance of various ceramic membrane filtration technologies designed and developed for the efficient treatment of PW generated from tank dewatering and several oily model systems.